HUBUNGAN MOTIVASI BELAJAR DAN SIKAP TERHADAP GURU PEMBIMBING DENGAN PRESTASI BELAJAR SISWA KELAS 8 DI SMP NEGERI 8 SURAKARTA - -, Fadlilah; Bisri (UNIBA Surakarta), Slamet Riyadi (Manajemen Bisnis Syariah, 2010)
This research objective are : 1) To understand the positive link of students learnmotivation with the achievement of students learn in SMP Negeri 8 Surakarta. 2) Tounderstand the positive link among student attitude to counselor teacher with theachievement of students learn in SMP Negeri 8 Surakarta. 3). To understand thecollectively positive link between among learn motivation and the attitude to counselorteacher with the achievement of students learn in SMP Negeri 8 Surakarta.Research method is descriptive with the correlation approach. For the hypothesis1 and hypothesis 2 is used the technique of coefficient correlation of product moment.For the hypothesis 3 is used the analysis of Doubled Linear Regression. To be searchedthe F count.The Population of this research are the students of SMP Negeri 8 Surakrta Class8 Semester 1 anomalous semester with 249 students. Taken sample are the students ofclass 8a until class 8f there are 100 students. Taken sample is used technique in thisresearch are Random Sampling which is consisted by minimize homogeneous set anumber so that each set of population getting same opportunity to be chosen as sample.With the sample of Simple Random Sampling means taken the sample from populationwhich is have the same opportunity to included as member sample which is obtainedfrom simple intake sample at random as much 100 responders.To test the first hypothesis is called there the positive link among learn studentsmotivation with the achievement of students in SMP Negeri 8 Surakarta, obtained bycalculation r equal to 0,728 and r with N=100 in significant level. 5% = 0,1279. So r xy xy> r . From this second hypothesis is called there is a positive link among students tableattitude to counselor teacher with the achievement of students learn in SMP Negeri 8Surakarta obtained by calculation F = 117,052 while F with N = 100 in significant hit tablelevel 5% = 3,9391. So F > F hit tableKey Word : learn motivation, attitude, achievement